Simulation and video feedback as catalysts linguistic skill development in psychology education - Diamanti, Roberta; Angelini, María Laura (Frontiers in Education, 2025)
IntroductionThis study investigates the effectiveness of simulation combined with video-assisted feedback as a pedagogical approach to improve linguistic competence, metacognitive awareness, and professional communication skills in psychology students learning English.MethodsA mixed-methods research design was employed involving 80 psychology students who participated in three iterative simulation cycles consisting of briefing sessions, recorded simulations, and structured video-assisted debriefings. Quantitative data were collected through a validated Likert-scale questionnaire and analyzed using Gaussian Graphical Models (GGM) to examine evolving relationships among professional experience, language proficiency, teamwork, motivation, and perceived utility of video-based feedback. Qualitative data were gathered from reflective reports, open-ended questions, and video observations and analyzed through thematic analysis.ResultsInitial findings indicated students primarily focused on overcoming linguistic barriers, perceiving language proficiency as a critical challenge. This indicates that language concerns were a primary impediment, potentially distracting from their ability to fully engage with the simulation’s learning objectives, such as mastering psychological terminology or practicing active listening skills. However, as the simulation cycles progressed, video-assisted feedback became central, with students actively seeking it to improve their interview techniques and diagnostic accuracy. This suggests that students increasingly viewed feedback as a valuable tool for self-assessment and skill development. For instance, qualitative data showed they began specifically requesting feedback on their ability to establish rapport with simulated clients and formulate accurate diagnoses, demonstrating increased metacognitive reflection. Thematic analysis of reflective reports corroborated these quantitative findings. Students’ comments shifted from initial anxieties about language to focused requests for feedback on specific professional skills. For example, students noted how watching their videos helped them identify nonverbal cues that conveyed empathy or areas where their questioning techniques could be improved, directly impacting their ability to regulate their learning and enhance professional performance.DiscussionThe findings underline the importance and effectiveness of integrating simulation with structured video-based feedback, demonstrating a clear shift from initial concerns about linguistic competence toward advanced metacognitive self-regulation and professional collaboration. These outcomes provide empirical support for simulation-based pedagogies and offer practical implications for educational practices in psychology curricula.